Clinical significance of LINC01158 in breast cancer and inhibition of proliferation and metastasis of breast cancer cells by regulating miR-711 - Xiaohe Lan; Zibai Guo; Linmei Lin; Wanqi Lin; Yi Zheng; Yabing Liu (Hereditas)
Abstract Objective Breast cancer (BC) has a poor prognosis due to metastasis and recurrence. LINC01158 is aberrantly expressed in breast cancer. Therefore, we investigated the regulatory mechanism and prognostic value of LINC01158 in BC. Methods 121 patients with BC were enrolled. LINC01158 and miR-711 levels were analyzed by RT-qPCR. Independent predictors of poor BC prognosis were analyzed by multifactorial Cox regression. Kaplan-Meier curves were used to analyze the 5-year survival rate of BC patients. DLR assay verified the relationship between LINC01158 and miR-711 target binding. CCK-8 was used to detect the proliferative capacity of cells. Transwell was used to analyze cell migration and invasion ability. Results In BC tissues and cell lines, LINC01158 expression was reduced and miR-711 levels were elevated. Low expression of LINC01158 resulted in a shortened overall survival of BC patients. LINC01158 binds to the miR-711 target and negatively correlates with the level of miR-711. Overexpression of LINC01158 decreased miR-711 levels and reduced BC cell proliferation, migration and invasion. In addition, Cox regression results showed that LINC01158 was an independent prognostic factor for BC. Conclusion LINC01158 may be a prognostic marker for BC. Increasing the expression level of LINC01158 could reduce the expression of miR-711, which could inhibit cell proliferation, migration and invasive behaviors, and has the potential to delay the progression of BC.